Relationships between Rodent White Adipose Fat Pads and Human White Adipose Fat Depots - Chusyd, Daniella E.; Wang, Donghai; Huffman, Derek M.; Nagy, Tim R. (Frontiers in Nutrition, 2016)
The objective of this review was to compare and contrast the physiological and metabolic profiles of rodent white adipose fat pads with white adipose fat depots in humans. Human fat distribution and its metabolic consequences have received extensive attention, but much of what has been tested in translational research has relied heavily on rodents. Unfortunately, the validity of using rodent fat pads as a model of human adiposity has received less attention. There is a surprisingly lack of studies demonstrating an analogous relationship between rodent and human adiposity on obesity-related comorbidities. Therefore, we aimed to compare known similarities and disparities in terms of white adipose tissue development and distribution, sexual dimorphism, weight loss, adipokine secretion, and aging. While the literature supports the notion that many similarities exist between rodents and humans, notable differences emerge related to fat deposition and function of white adipose tissue. Thus, further research is warranted to more carefully define the strengths and limitations of rodent white adipose tissue as a model for humans, with a particular emphasis on comparable fat depots, such as mesenteric fat.